The Role of the Nurses in Elderly Health Promotion - อ่อนศรี, ปราณี; อุไรเลิศ, อัจฉรา (Journal of The Royal Thai Army Nurses, 2018)
Nowadays, Thailand move toward aged society. There are changed in elderly about physical, mental and society. Elderly health promotion involves elderly persons and their families. Moreover, Nurses are very important in elderly health promotion. Elderly health promotion is the process of enabling people to increase control over, and to improve their health. To reach a state of complete physical, mental and social well-being, an individual or group must be able to identify and to realize aspirations and needs, including capability to adapt with the environment. Ottawa charter is a crucial strategy of health promotion: build healthy public policy, create supportive environments, strengthen community action, develop personal skills and reorient health services.